BIBLIO COUNSELING TO REDUCE THE EFFECTIVENESS OF STUDENT academic procrastination FORCE OF GUIDANCE AND COUNSELING - Erik Teguh Prakoso; Wida Reni Kristianti (Satya Widya, 2017)
Academic Procrastination is a manifestation form of avoidance in a task that should be done by an individual. Procrastinator deliberately to delay the work or tasks that should be solved. Thus procrastination is delay work on an employment or assignment that is done deliberately.This study uses a quantitative approach to design Quasi Experiment patterns pretest and posttest Group.The subjects in this study is the Student Guidance and Counseling Program 2015 University Kanjuruhan Malang forces amounting to 5 students. The research instrument uses a scale of academic procrastination. Data analysis technique used is statistically using SPSS 22:00 for windows.The results showed that based on the analysis of different test Wilcoxon between pretest and posttest generate value significant (two-tailed) <0.05 is 0.043, which means the provision of treatment through counseling biblio effective to reduce the level of student academic procrastination. Based on the results of data presentation can be concluded that the study subjects experienced the difference after the treatment is done, so it can be said that the biblio effective counseling to reduce the level of academic procrastination. Keywords: Academic Procrastination, Biblio counseling